Rancang Bangun Sistem Informasi Pengaduan Perbaikan Jalan Berbasis Website : Design and Development of a Website-Based Road Repair Complaints Information System - Aprianto Tandi Kamma; Cristian Dwi Suhendra; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2024)
Improving the quality of road infrastructure is one of the main priorities in regional development, especially in ensuring the comfort and safety of road users. Road damage that is not immediately repaired can disrupt community activities and increase the risk of accidents, ranging from potholes to serious damage. Therefore, a system is needed to report and receive road damage. Therefore, the author designed and built a website-based road repair complaint information system using the Laravel framework and MYSQL database. With this system, it is hoped that it will make it easier for the public to report road damage in real-time and assist relevant agencies in managing and authenticating reports quickly and transparently.